Mary Rudenberg, Music Therapist Pioneer - Neugebauer, Christine (Voices: A World Forum for Music Therapy, 2010)
It was during my training when I came to understand and appreciate the knowledge base and experience that Mary Rudenberg has contributed to the field of music therapy. Medical music therapy was still in its infancy and the music therapy internship program at the University of Texas Medical Branch in Galveston, Texas was one of a few internships in the nation offering music therapy training in a medical setting.